2013
DOI: 10.1128/aem.00229-13
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fucosyl- N -Acetylglucosamine Disaccharides by Transfucosylation Using α-l-Fucosidases from Lactobacillus casei

Abstract: bAlfB and AlfC ␣-L-fucosidases from Lactobacillus casei were used in transglycosylation reactions, and they showed high efficiency in synthesizing fucosyldisaccharides. AlfB and AlfC activities exclusively produced fucosyl-␣-1,3-N-acetylglucosamine and fucosyl-␣-1,6-N-acetylglucosamine, respectively. The reaction kinetics showed that AlfB can convert 23% p-nitrophenyl-␣-L-fucopyranoside into fucosyl-␣-1,3-N-acetylglucosamine and AlfC at up to 56% into fucosyl-␣-1,6-N-acetylglucosamine. Fucosyl-oligosaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 25 publications
0
51
0
3
Order By: Relevance
“…). Fucosylated oligosaccharides are involved in numerous and crucial physiological processes such as the immune response, signal transduction, early embryogenesis and development, growth regulation, apoptosis, adhesion of pathogens, extravasation of leukocytes, maturation and interaction of gametes, and pathological processes, including arteriosclerosis and cancer .…”
Section: Importance Of Fucosylated Oligosaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…). Fucosylated oligosaccharides are involved in numerous and crucial physiological processes such as the immune response, signal transduction, early embryogenesis and development, growth regulation, apoptosis, adhesion of pathogens, extravasation of leukocytes, maturation and interaction of gametes, and pathological processes, including arteriosclerosis and cancer .…”
Section: Importance Of Fucosylated Oligosaccharidesmentioning
confidence: 99%
“…These fucosidases were named AlfA, AlfB, and AlfC. The last two were evaluated for transfucosylation using pNP‐Fuc as the donor and GlcNAc as the acceptor . It was found that AlfB transfers fucose with the formation of α‐1,3 bonds, synthesizing α‐ l ‐Fuc‐(1–3)‐β‐ d ‐GlcNAc with a yield of 23%.…”
Section: Bacterial Fucosidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two putative rho-independent terminators were identified downstream of alfC (ΔG, Ϫ13.5 kcal/mol) and sugK (ΔG, Ϫ17.0 kcal/mol). The high specificity of the ␣-L-fucosidase AlfC from L. casei BL23 for ␣1,6 linkages such as those present at fucosyl-oligosaccharides (45,47), together with the sequence analysis of the alf-2 cluster, particularly the presence of a gene coding for a hypothetical N(4)-(␤-N-acetylglucosaminyl)-L-asparaginase, suggested that the alf-2 operon could be involved in the metabolism of the core 6=FN-Asn ( Fig. 1).…”
mentioning
confidence: 99%
“…To test this hypothesis, this glycoamino acid was synthesized by transfucosylation with the ␣-L-fucosidase AlfC. We had previously utilized AlfC in transglycosylation reactions with p-nitrophenyl-␣-Lfucopyranoside (pNP-fuc) as the donor and GlcNAc as the acceptor to produce 6=FN (47). Here, the ability of AlfC to use GlcNAc-Asn as the acceptor was tested, and 6=FN-Asn was synthesized and purified.…”
mentioning
confidence: 99%